Impact of Climate Variability on Maize Production in South Africa - Matandirotya, Newton R.; Manjeru, Pepukai; Cilliers, Dirk P; Burger, Roelof P; Mushore, Terrerence Darling (Springer, 2022)
Maize (Zea mays L.) is a staple food for most people in the Sub-Saharan Africa (SSA) region including South Africa. Climate models are predicting a 1.5–2 °C temperature rise compared to pre-industrial times. This temperature rise has the potential to negatively affect maize production. The purpose of this study was to explore the relationship between climatic elements and maize production from two regions of South Africa- the Highveld represented by the Free state province and the Lowveld represented by Limpopo province over the period 2007–2018. The highest planted hectarage was from the Highveld at 855,000 ha for white maize and 365,000 ha for yellow maize. Correspondingly, the same province produced the highest output per hectare of both white and yellow maize at 4745.25 tonnes and 2208.3 tonnes respectively. Yellow maize yielded a maximum of 8 tonnes per hectare (2016/2017) while for white maize the maximum was 7.5 tonnes per hectare in 2016/2017 as well as 2017/2018 seasons on the Lowveld. A linear regression analysis between maize production and area grown indicated a positive strong association for both regions at (r2 = 0.60) for Highveld and (r2 = 0.57) for Lowveld respectively. For yellow maize, a weak positive relationship was established on the Highveld at (r2 = 0.26) while a very strong association was established in the Lowveld at (r2 = 0.85). To increase maize output, there is a need to shift from a rain-dependent type of production to a mixed approach where irrigation systems are also infused.